Arbuscular Mycorrhizas Alleviate Plant Stress : Analysis of Studies from South America - Pagano, Marcela Claudia (2013)
Fil: Pagano, Marcela Claudia. Department of Physics. Federal University of Minas Gerais; Belo Horizonte; Minas Gerais; Brazil